The inside scoop on eating disorder recovery : advice from two therapists who have been there - Reichmann, Colleen; Rollin, Jennifer (New York, NY : Routledge, 2021)
"The Inside Scoop on Eating Disorder Recovery is a fresh, smart, how-to book that helps people with eating disorders to heal their relationship with food, their bodies, and ultimately themselves. Written from the perspective of two eating disorder therapists, both of whom are recovered from their own eating disorders, the text uses humor, personal narratives, and research-proven techniques to offer specific actionable guidelines on how to reclaim one's life from an eating disorder. The authors explain the difference between dieting and eating disorders, break down the stages of recovery, and provide tips on how to thrive in each stage. The book provides powerful myth-busting on topics that have historically not been addressed in eating disorder recovery books, such as clean eating and orthorexia, exercising in recovery, and how to use social media in a pro-recovery way. Tangible exercises at the end of each chapter provide readers with advice and tips on implementing this approach to recovery in their day-to-day lives The humorous and down-to-earth tone of the book creates an authentic and genuine feel that leaves those who struggle with chronic dieting, eating disorders, and negative body image feeling connected and heard"--
Introduction Chapter 1: Am I Just Dieting? How to Tell When the Line Has Been Crossed Chapter 2: Challenging "Not Sick Enough" Chapter 3: Early Recovery: Changing Your Behaviors Chapter 4: Changing Your Thoughts: Legalize It -- Food, That Is! Chapter 5: All about Those Feels: Why Emotions Matter Chapter 6: Binge Eating: No, it's Not about 'Willpower' Chapter 7: Health at Every Size: The MVP of Eating Disorder Recovery Chapter 8: Fat Positivity: A Game Changer Chapter 9: Trauma: Taking Back Your Power Chapter 10: Orthorexia: The Eating Disorder that Hides in Plain Sight Chapter 11: Getting Unstuck: The Trap of Partial Recovery Chapter 12: All in the Fam: Where Do Our Loved Ones Come in? Chapter 13: Body Image Chapter 14: Gym-Timidation: How to Move for Joy Chapter 15: Intuitive Eating Chapter 16: Finding Meaning Chapter 17: Summary
OCLC-licensed vendor bibliographic record.
Keywords: Eating disorders -- Treatment -- Popular works; PSYCHOLOGY / Psychopathology / Eating Disorders